"But Oh! What Tales": Portraying the Middle East in U.S. Homophile Periodicals of the 1950s and 1960s. Issue 7 (7th June 2017) - Milo, Marva
ABSTRACT: This essay examines Middle East representations in U.S. homophile periodicals from 1953 to 1964. The essay uses more than 120 Middle East–related items that were published in ONE, Mattachine Review, and The Ladder to address the periodicals' engagement with the region (particularly ancient history and biblical themes) and discuss the types of sexual "knowledge" that the homophile periodicals created about the region. It then assesses the role of periodicals as a genre in the creation of a transnational homophile community, showing both their potential for democratizing participation in this community and their limits. The essay argues that the periodicals made visible the process of assembling a homosexual identity and the fragmentary nature of the parts it strove to unify. Though the views of key U.S. homophile organizations became hegemonic in the international gay rights movement, the periodicals show a more complex, ambivalent, and contested process.